Surface-modified Cu-based catalyst, preparation method thereof and application of the catalyst in preparation of ethanol from CO hydrogenation
By employing a surface-modified Cu-based catalyst preparation method and utilizing the synergistic design of copper salts, transition metal salts, tin solutions, lithium niobate, and multi-amino metal-organic framework materials, the problems of low ethanol selectivity and insufficient stability of Cu-based catalysts in the CO hydrogenation to ethanol process were solved, achieving high CO conversion rate and ethanol selectivity.
Patent Information
- Application Number
- CN202511469693.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-10-15
- Publication Date
- 2025-12-23
- Estimated Expiration
- 2045-10-15
AI Technical Summary
Existing Cu-based catalysts suffer from low ethanol selectivity and insufficient stability in the process of CO hydrogenation to ethanol, especially under high temperature and high pressure conditions, the active components are prone to sintering and deactivation.
By employing a surface-modified Cu-based catalyst preparation method, and through the synergistic design of copper salts, transition metal salts, dispersants, tin solutions, lithium niobate, and multi-amino metal-organic framework materials, a Cu-Sn interface and oxygen vacancies are formed, which inhibits Cu particle agglomeration, promotes CC coupling reaction, and reduces water-gas change reaction.
It achieves a synergistic improvement in activity, selectivity and stability in the CO hydrogenation to ethanol reaction, improves the catalyst conversion rate and ethanol selectivity, reduces the surface free energy of the active component, and is suitable for large-scale production.
Smart Images

Figure CN120939996B_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of catalyst preparation, in particular to a surface-modified Cu-based catalyst, a preparation method thereof and application thereof in CO hydrogenation to ethanol. BACKGROUND
[0002] As an important clean fuel and chemical raw material, the efficient preparation technology of ethanol has always been a research hotspot. Common ethanol preparation methods include grain fermentation method and coal-based ethanol method. The grain fermentation method is too wasteful and low in efficiency, and the coal-based ethanol process route is complex and produces a large amount of carbon dioxide. In comparison, the CO or CO2 hydrogenation to ethanol technology uses CO or CO2 as raw material, has a wide source and can realize efficient utilization of carbon resources, and has a good development prospect.
[0003] In the research of CO or CO2 hydrogenation to ethanol, the catalyst is the core. In the prior art, a variety of catalyst systems have been developed, such as rhodium-based catalyst, iron-based catalyst and copper-based catalyst. Although the rhodium-based catalyst has high ethanol selectivity, it is expensive and scarce in resources, which is not conducive to large-scale application; the iron-based catalyst generates a large amount of hydrocarbon by-products in the reaction, and has low ethanol selectivity. The copper-based catalyst is concerned due to its low cost and certain activity for CO hydrogenation reaction, but it still has many problems in practical application.
[0004] Specifically, the prior art has the following deficiencies: first, the reaction selectivity and conversion rate are difficult to balance. Since the CO hydrogenation to ethanol reaction is complex, involving CO dissociation activation, C-C coupling and step-by-step hydrogenation, etc., each path competes with each other, resulting in that most catalysts have low ethanol selectivity at high conversion rate, or have poor conversion rate at high selectivity, and the catalyst stability is insufficient. Many catalysts, especially single-atom catalysts, are prone to sintering and deactivation of active components due to high surface free energy under high temperature and high pressure reaction conditions, affecting their long-term performance. SUMMARY
[0005] The present application provides a surface-modified Cu-based catalyst, a preparation method thereof and application thereof in CO hydrogenation to ethanol, to solve the problem of low ethanol selectivity in the related art.
[0006] In a first aspect, a preparation method of a surface-modified Cu-based catalyst is provided, characterized in that it comprises the following steps:
[0007] S1, precursor solution preparation: dissolve copper salt and transition metal salt in deionized water, add dispersant and paraffin under stirring, heat to 58-60℃ and continuously stir for 1-2h to obtain a precursor solution;
[0008] S2, preparation of xerogel:
[0009] The carrier is added into the precursor solution according to a solid-liquid ratio of 1:(10-15), ultrasonic dispersion is performed for 20-30 min, a precipitant is added dropwise under stirring, and pH is adjusted to 7.5, so as to obtain a gel-like compound;
[0010] The gel-like compound is aged at room temperature for 4-5 h, and then dried at 75-80 °C for 12-14 h, so as to obtain a dry gel;
[0011] S3, modification:
[0012] S301, loading: the dry gel is immersed into a tin solution according to a solid-liquid ratio of 1:(2-10), stirred at 30-50 °C for 2-3 h, washed with deionized water after filtration, and dried at 75-80 °C for 3-4 h, so as to obtain a loaded dry gel, and the concentration of the tin solution is 0.2 mol / L;
[0013] S302, lithium niobate modification: lithium niobate is mixed with the loaded dry gel, and deionized water is added for ball milling for 2-3 h, the mass of the deionized water is twice that of the dry gel, and the ball milling speed is 300 r / min;
[0014] S303, hybrid modification: after a polyamino metal organic framework material is dissolved in 10 wt% triethanolamine, the sample prepared in S302 is added, ultrasonic treatment is performed for 1-2 h, and then vacuum drying is performed at 110-120 °C for 10-12 h, so as to obtain a modified catalyst;
[0015] S4, preparation of a surface-modified Cu-based catalyst:
[0016] The modified catalyst is placed in a tube furnace, heated to 180-200 °C at a rate of 2 °C / min under a reducing atmosphere, and then kept at 180-200 °C for 2-3 h, and then heated to 300-350 °C at a rate of 1 °C / min, and then kept at 300-350 °C for 2-3 h, and then cooled to room temperature, so as to obtain a surface-modified Cu-based catalyst.
[0017] Preferably, in S1, the addition ratio of the copper salt and the transition metal salt is a molar ratio of copper to transition metal of (8-10):1; and the total molar ratio of the dispersant to metal ions, including copper and transition metal, is (0.2-0.5):1.
[0018] Preferably, the copper salt is one of copper nitrate, copper sulfate and copper chloride;
[0019] The transition metal salt is one of zinc nitrate, aluminum nitrate and zirconium nitrate;
[0020] The dispersant is ethylene glycol or citric acid.
[0021] Preferably, in the S2, the carrier is mesoporous SiO2, and the precipitant is 2 mol / L ammonia water or 10 wt% sodium carbonate solution.
[0022] Preferably, in the S301, the tin solution is one of a tin chloride solution, a stannous chloride solution, and a tin oxalate solution.
[0023] Preferably, in the S302, the lithium niobate is weighed according to a tin species to lithium niobate mass ratio (5-8):1, and the mass of the tin species is calculated according to the mass difference before and after the dry gel is loaded in the S301.
[0024] Preferably, in the S303, the mass ratio of the polyamino metal organic framework material to the sample prepared in the S302 is (0.1-0.2):1, and the polyamino metal organic framework material is zirconium aminophthalate.
[0025] The mass ratio of the zirconium aminophthalate to 10 wt% triethanolamine solution is 1:20.
[0026] In a second aspect, a surface-modified Cu-based catalyst is provided, which is prepared by the preparation method of the surface-modified Cu-based catalyst according to any one of the above.
[0027] In a third aspect, the surface-modified Cu-based catalyst is applied to CO hydrogenation to prepare ethanol.
[0028] The technical scheme provided in the present application has the following beneficial effects:
[0029] The present application provides a surface-modified Cu-based catalyst, a preparation method thereof, and application of the catalyst in CO hydrogenation to prepare ethanol. Copper serves as a catalytically active center core, transition metals optimize the electron density of Cu through electron transfer, enhance the adsorption and activation capacity of Cu to CO molecules, and at the same time, the transition metals act as a structure promoter to inhibit the agglomeration of Cu particles during preparation and reaction, maintain high-dispersed active sites, and lay a foundation for the improvement of CO conversion rate. Tin species is loaded on the surface of the catalyst to form a stable Cu-Sn interface with Cu, the acid sites of SnOx species (such as SnO2) can promote the C-C coupling reaction of intermediates, lithium niobate is coated on the surface of the catalyst by grinding, and the oxygen vacancies thereof can capture trace amounts of water generated in the reaction, thereby inhibiting the excessive dissociation of CO to generate methane and effectively reducing the water-gas shift reaction (carbon monoxide and water generate carbon dioxide and hydrogen). The polyamino metal organic framework forms coordination bonds with Cu and Sn through amino groups, thereby reducing the surface free energy of the active components. The present application realizes the synergistic improvement of activity, selectivity, and stability in the CO hydrogenation to prepare ethanol through multi-component synergistic design and step-by-step modification. BRIEF DESCRIPTION OF DRAWINGS
[0030] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings needed to be used in the embodiment description will be briefly introduced. Obviously, the drawings in the following description are only some embodiments of the present application, and other drawings can be obtained by those skilled in the art without any creative effort.
[0031] Figure 1 Preparation flow chart of the surface-modified Cu-based catalyst provided by the present application;
[0032] Figure 2 XRD pattern of the surface-modified Cu-based catalyst prepared in Example 1 to Example 4 provided by the present application. DETAILED DESCRIPTION
[0033] In order to make the objects, technical solutions and advantages of the embodiments of the present application clearer, the technical solutions in the embodiments of the present application will be described clearly and completely in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are only some of the embodiments of the present application, rather than all the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without any creative effort fall within the scope of protection of the present application.
[0034] Referring to Figures 1-2 As shown in the drawings, the present application provides a surface-modified Cu-based catalyst, a preparation method thereof and an application thereof in the preparation of ethanol from CO hydrogenation.
[0035] Example 1
[0036] The preparation method of the surface-modified Cu-based catalyst provided in the present embodiment comprises the following steps:
[0037] S1, preparation of a precursor solution: 60.02 g of copper nitrate and 15.46 g of zinc nitrate were dissolved in 390.32 g of deionized water, 34.2 g of citric acid and 6 g of paraffin were added under stirring, the temperature was raised to 60℃ and the stirring was continued for 1 h to obtain a precursor solution;
[0038] S2, preparation of a xerogel:
[0039] 20 g of mesoporous SiO2 with an average particle size of 50 nm and a specific surface area of 500 m 2 / g were added into 240 g of the precursor solution prepared in S1, ultrasonic dispersion was performed for 30 min, 2 mol / L of ammonia water was added dropwise under stirring, and the pH was adjusted to 7.5 to obtain a gel-like composite;
[0040] The gel-like composite was aged at room temperature for 5 h, and then dried at 80℃ for 14 h to obtain a xerogel;
[0041] S3, modification:
[0042] S301, loading: 20 g of the dry gel prepared in S2 was immersed in 40 mL of a stannous chloride solution with a concentration of 0.2 mol / L, stirred at 40°C for 2 h, washed with deionized water after filtration, and dried at 80°C for 4 h to obtain a loaded dry gel with a weight of 29.7 g;
[0043] S302, lithium niobate modification: 1.4 g of lithium niobate was mixed with 29.7 g of the loaded dry gel, and 60 mL of deionized water was added and ball-milled at a speed of 300 r / min for 2 h;
[0044] S303, hybrid modification: 5 g of zirconium amino benzene dicarboxylate was dissolved in 100 g of triethanolamine with a concentration of 10 wt%, and 30 g of the sample prepared in S302 was added, ultrasonically treated for 2 h, and vacuum dried at 120°C for 10 h to obtain a modified catalyst;
[0045] S4, preparation of a surface-modified Cu-based catalyst:
[0046] The modified catalyst was placed in a tube furnace, heated to 200°C at a rate of 2°C / min under a reducing atmosphere, and held for 2 h. Then, the temperature was increased to 350°C at a rate of 1°C / min, and held for 3 h. After cooling to room temperature, a surface-modified Cu-based catalyst was obtained.
[0047] Example 2
[0048] The difference from Example 1 is that the volume of the stannous chloride solution added in S301 is 83 mL.
[0049] Example 3
[0050] The difference from Example 1 is that the volume of the stannous chloride solution added in S301 is 125 mL.
[0051] Example 4
[0052] The difference from Example 1 is that the volume of the stannous chloride solution added in S301 is 166 mL.
[0053] Example 5
[0054] The preparation method of the surface-modified Cu-based catalyst provided in this example includes the following steps:
[0055] S1, preparation of a precursor solution: 106.5 g of copper sulfate, 35.8 g of zinc nitrate, 28.8 g of citric acid, and 10.65 g of paraffin were dissolved in 828.9 g of deionized water, and stirred at a temperature of 58°C for 1 h to obtain a precursor solution;
[0056] S2, Preparation of dry gel:
[0057] 30 g of mesoporous SiO2 with an average particle size of 50 nm and a specific surface area of 500 m 2 / g was added to 300 g of the precursor solution prepared in S1 above, ultrasonic dispersion was performed for 20 min, 2 mol / L ammonia water was added dropwise under stirring, and the pH was adjusted to 7.5 to obtain a gel-like composite;
[0058] The gel-like composite was aged at room temperature for 4 h, and then dried at 75 °C for 12 h to obtain a dry gel;
[0059] S3, Modification:
[0060] S301, Loading: 20 g of the dry gel prepared in S2 above was immersed in 200 mL of a tin chloride solution with a concentration of 0.2 mol / L, stirred at 40 °C for 3 h, washed with deionized water until there was no chloride ion in the filtrate (determined by silver nitrate), and then dried at 75 °C for 3 h to obtain a loaded dry gel with a weight of 28.8 g;
[0061] S302, Lithium Niobate Modification: 1.1 g of lithium niobate was mixed with 28.8 g of the loaded dry gel, and 57.6 mL of deionized water was added, and ball milling was performed at a speed of 300 r / min for 2 h;
[0062] S303, Hybrid Modification: 2.5 g of zirconium aminobenzenedicarboxylate was dissolved in 50 g of triethanolamine with a concentration of 10 wt%, and then 25 g of the sample prepared in S302 above was added, ultrasonic treatment was performed for 2 h, and then vacuum drying was performed at 110 °C for 12 h to obtain a modified catalyst;
[0063] S4, Preparation of Surface-Modified Cu-Based Catalyst:
[0064] The modified catalyst was placed in a tube furnace, heated to 180 °C at a rate of 2 °C / min under a reducing atmosphere, and then held for 3 h, and then heated to 300 °C at a rate of 1 °C / min, and then held for 2 h, and then cooled to room temperature to obtain a surface-modified Cu-based catalyst.
[0065] Example 6
[0066] The preparation method of the surface-modified Cu-based catalyst provided in this example includes the following steps:
[0067] S1, Preparation of precursor solution: 99.5 g of copper chloride and 27.8 g of aluminum nitrate were dissolved in 400 g of deionized water, 15.2 g of citric acid and 9.95 g of paraffin were added under stirring, the temperature was increased to 60 °C, and stirring was continued for 2 h to obtain a precursor solution;
[0068] S2, Preparation of dry gel:
[0069] 30 g of mesoporous SiO2 with an average particle size of 50 nm and a specific surface area of 500 m 2 / g was added to 450 g of the precursor solution prepared in S1, ultrasonic dispersion was performed for 30 min, a 10 wt% sodium carbonate solution was added dropwise under stirring, the pH was adjusted to 7.5, and a gel-like composite was obtained;
[0070] The gel-like composite was aged at room temperature for 4 h, and then dried at 78 °C for 13 h to obtain a xerogel.
[0071] S3, modification:
[0072] S301, loading: 20 g of the xerogel prepared in S2 was immersed in 60 mL of a tin oxalate solution with a concentration of 0.2 mol / L, stirred at 50 °C for 2.5 h, washed with deionized water until there was no chloride ion in the filtrate (determined by silver nitrate), and then dried at 78 °C for 3.5 h to obtain a loaded xerogel with a weight of 32.5 g.
[0073] S302, lithium niobate modification: 2.5 g of lithium niobate was mixed with 32.5 g of the loaded xerogel, 60 mL of deionized water was added, and ball milling was performed at a speed of 300 r / min for 3 h; 35 g
[0074] S303, hybrid modification: 6 g of zirconium amino benzene dicarboxylate was dissolved in 120 g of a triethanolamine solution with a concentration of 10 wt%, 30 g of the sample prepared in S302 was added, ultrasonic treatment was performed for 1 h, and then vacuum drying was performed at 105 °C for 11 h to obtain a modified catalyst.
[0075] S4, preparation of a surface-modified Cu-based catalyst:
[0076] The modified catalyst was placed in a tube furnace, heated to 200 °C at a rate of 2 °C / min under a reducing atmosphere, and then held for 2 h. The temperature was then increased to 320 °C at a rate of 1 °C / min, and then held for 2.5 h. After cooling to room temperature, a surface-modified Cu-based catalyst was obtained.
[0077] The surface-modified Cu-based catalysts prepared in Examples 1-6 (hereinafter referred to as modified catalysts) were applied to a fixed-bed CO hydrogenation reaction to produce ethanol, and the reaction conditions were as follows: a reaction temperature of 220-260 °C, a molar ratio of CO to H2 of 1:(3-4), an inert gas N2 content of 5%, a reaction pressure of 3-5 MPa, and a gas hourly space velocity (GHSV) of 1000-3000 h -1 .
[0078] Specifically, the specific application conditions of the catalysts prepared in Examples 1-6 are shown in Table 1.
[0079] Table 1 Application conditions of the catalysts prepared in Examples 1-6
[0080]
[0081] The specific conversion rates of the catalysts obtained in Examples 1-6 are shown in Table 2.
[0082] Table 2. Conversion and selectivity of the catalysts prepared in Examples 1-6
[0083]
[0084] As can be seen from Table 2, the CO conversion rate of Examples 5-6 is lower than that of Examples 1-4, which to some extent indicates that the catalysts prepared in Examples 5 and 6 have fewer active sites.
[0085] This is because the tin solution used in Examples 1-4 is stannous chloride, which effectively reduces the water-gas change reaction and results in a higher CO conversion rate. The reaction conditions for the catalysts prepared in Examples 1-4 are consistent; under these conditions, further details can be found... Figure 2 The image shows the XRD patterns of the catalysts prepared in Examples 1-4. Cat-Sn x In this context, x represents the percentage of Sn in the total metal content of the catalyst. For example, Cat-Sn2 means that Sn accounts for 2% of the total metal content of the catalyst.
[0086] As can be seen, three distinct diffraction peaks appeared at 43.29°, 50.43°, and 74.13°, corresponding to the (111), (200), and (220) planes of metallic Cu, respectively. A weak peak for carbon was observed at 23.6°, indicating that the liquid paraffin had decomposed. No ZnO signal peak was observed, suggesting that ZnO existed in an amorphous form or was below the detection limit of XRD. The presence of SnO2 diffraction peaks in the Cat-Sn8 catalyst may be due to excessive Sn causing uneven dispersion.
[0087] In the catalyst prepared in this application, copper serves as the core of catalytic activity, and transition metals act as structural promoters to inhibit the agglomeration of Cu particles during preparation and reaction, maintaining highly dispersed active sites. Tin species are uniformly loaded onto the catalyst surface through impregnation, forming a stable Cu-Sn interface with Cu. The acidic sites of SnOx species (such as SnO2) can promote the CC coupling reaction of intermediates, directionally generating ethanol rather than methanol or long-chain hydrocarbons, laying the foundation for improving CO conversion.
[0088] The lithium niobate is coated on the surface of the catalyst by grinding, the layered crystal structure of the lithium niobate can physically isolate the Cu-Sn active sites, and reduce the particle migration and sintering at high temperature; meanwhile, the oxygen vacancies of the lithium niobate can capture trace water generated in the reaction, and avoid the erosion of the water to the Cu active center; the polyamino metal organic framework forms coordination bonds with Cu and Sn through the amino groups, reduces the surface free energy of the active components, and inhibits the agglomeration in the reaction process. Meanwhile, the overall preparation process of the catalyst does not need high-precision equipment, and all the raw materials are industrial-grade conventional chemicals, which is suitable for large-scale production.
[0089] The above description is merely a specific implementation of the present application, which enables those skilled in the art to understand or implement the present application. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present application. Therefore, the present application will not be limited to these embodiments shown herein, but will conform to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A method for preparing a surface-modified Cu-based catalyst, characterized by, It comprises the following steps: S1, precursor solution preparation: dissolve copper salt and transition metal salt in deionized water, add dispersant and paraffin under stirring, heat to 58-60 DEG C and continue stirring for 1-2h, to obtain the precursor solution; the transition metal salt is one of zinc nitrate and zirconium nitrate; S2, preparation of dry gel: The carrier is added to the precursor solution according to the solid-liquid ratio of 1g:(10-15)g, ultrasonic dispersion for 20-30min, drop the precipitant under stirring, adjust the pH to 7.5, to obtain the gel-like compound; The gel-like compound is aged at room temperature for 4-5h, and then dried at 75-80 DEG C for 12-14h to obtain the dry gel; S3, modification: S301, loading: the dry gel is immersed in a tin solution according to the solid-liquid ratio of 1g:(2-10)mL, stirred at 30-50 DEG C for 2-3h, washed with deionized water after filtration, and dried at 75-80 DEG C for 3-4h to obtain the loaded dry gel, the concentration of the tin solution is 0.2mol / L; S302, lithium niobate modification: mix lithium niobate with the loaded dry gel, add deionized water and ball mill for 2-3h, the mass of the deionized water is twice that of the dry gel, and the ball mill speed is 300r / min; S303, hybrid modification: dissolve the polyamino metal organic framework material in 10wt% triethanolamine, add the sample prepared in S302, ultrasonic treatment for 1-2h, and vacuum drying at 110-120 DEG C for 10-12h to obtain the modified catalyst; The polyamino metal organic framework material is zirconium aminobenzenedicarboxylate; S4, preparation of surface modified Cu-based catalyst: The modified catalyst is placed in a tube furnace, heated to 180-200 DEG C at a rate of 2 DEG C / min under a reducing atmosphere, and then kept for 2-3h, and then heated to 300-350 DEG C at a rate of 1 DEG C / min, and kept for 2-3h, and then cooled to room temperature to obtain the surface modified Cu-based catalyst.
2. The preparation method of the surface modified Cu-based catalyst according to claim 1, wherein: In S1, the addition ratio of copper salt and transition metal salt is the molar ratio of copper to transition metal (8-10):1; the total molar ratio of dispersant to metal ion (0.2-0.5):1, and the metal ion includes copper and transition metal.
3. The preparation method of the surface modified Cu-based catalyst according to claim 1 or 2, wherein: The copper salt is one of copper nitrate, copper sulfate and copper chloride; The dispersant is ethylene glycol or citric acid.
4. The preparation method of the surface modified Cu-based catalyst according to claim 1, wherein: In S2, the carrier is mesoporous SiO2, and the precipitant is 2mol / L ammonia water or 10wt% sodium carbonate solution.
5. The preparation method of the surface modified Cu-based catalyst according to claim 1, wherein: In S301, the tin solution is one of stannic chloride solution, stannous chloride solution and tin oxalate solution.
6. The method for preparing the surface-modified Cu-based catalyst according to claim 1, wherein: In S302, the lithium niobate is weighed according to the mass ratio of the tin species to the lithium niobate (5-8):1, and the mass of the tin species is calculated according to the mass difference before and after the dry gel is loaded in S301.
7. The method for preparing the surface-modified Cu-based catalyst according to claim 1, wherein: In S303, the mass ratio of the polyamino metal organic framework material to the sample prepared in S302 is (0.1-0.2):1; The mass ratio of the zirconium amino benzene dicarboxylate to the 10wt% triethanolamine solution is 1:
20.
8. A surface-modified Cu-based catalyst, characterized by, The surface-modified Cu-based catalyst is prepared by the method for preparing the surface-modified Cu-based catalyst according to any one of claims 1-7.
9. The application of the surface-modified Cu-based catalyst according to claim 8 in the CO hydrogenation to ethanol.
Citation Information
Patent Citations
Catalyst for preparing higher alcohol through CO2 hydrogenation and preparation method and application of catalyst
CN115400763A
Method for producing ethanol through electrocatalytic reduction of carbon dioxide and membrane coupling
CN120099542A